Toponyms and place heritage as sources of place brand value - Paula Sjöblom; Ulla Hakala (Debrecen University Press, 2022)
Commercial producers have long seen the advantage of branding their products, and the idea of branding also attracts place managers. In general, the core component of a brand is its name. In place branding, the name is even more crucial. It marks a geographical entity and creates the identity and image of the place. Having stayed unchanged, it represents longevity and stability and can be regarded as the place’s memory. In addition, place names carry of strong emotional attachment. The longer the history behind a name, the more meaningful it is as a word. A strong place brand is built upon a strong place heritage. Heritage is acknowledged as one of the future priorities in branding research. It is one of the intangible factors, in other words associations that differentiate brands from each other and are a source of tangible prosperity. Many of these associations are susceptible to competitor copying them – however, not the heritage or the name.
This paper will introduce the conceptualisation of place heritage, with the place name being one of the focal components. For this, we will use data from our previous empirical survey carried out in 2013 on the 28 municipalities in Southwestern Finland. This survey investigated residents’ attitudes towards municipality names and name changes. Herein, we will focus on answers to two statements in the survey – The name of my place of domicile is important to me, and A name change will weaken the sense of community and solidarity in the municipality – and correlations between them and the place heritage value of each municipality. The purpose of this paper is to demonstrate the importance of a place name in reference to place heritage value and to show an example of utilising this value in place branding.